2014
DOI: 10.1155/2014/246871
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, Purification, and Characterization of Glutaredoxin from Antarctic Sea-Ice BacteriumPseudoalteromonassp. AN178

Abstract: Glutaredoxins (Grxs) are small ubiquitous redox enzymes that catalyze glutathione-dependent reactions to reduce protein disulfide. In this study, a full-length Grx gene (PsGrx) with 270 nucleotides was isolated from Antarctic sea-ice bacterium Pseudoalteromonas sp. AN178. It encoded deduced 89 amino acid residues with the molecular weight 9.8 kDa. Sequence analysis of the amino acid sequence revealed the catalytic motif CPYC. Recombinant PsGrx (rPsGrx) stably expressed in E. coli BL21 was purified to apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Cold-active microbial enzymes have attracted increasing attention in recent years ( Wang et al, 2012 ). In addition to the properties related to their structural characteristics, one of the main advantages related to the use of these enzymes is the decrease energy expenditure and processing costs associated with industrial heating steps ( Duarte et al, 2013 ).…”
Section: Biotechnological Potentialmentioning
confidence: 99%
“…Cold-active microbial enzymes have attracted increasing attention in recent years ( Wang et al, 2012 ). In addition to the properties related to their structural characteristics, one of the main advantages related to the use of these enzymes is the decrease energy expenditure and processing costs associated with industrial heating steps ( Duarte et al, 2013 ).…”
Section: Biotechnological Potentialmentioning
confidence: 99%
“…These results were similar to Grxs from C. sorokiniana, 21 potato, 22 and Pseudoalteromonas. 23 It was previously reported that Populus trichocarpa thioredoxin (Trx h4) could be the substrate of E. coli Grxs. 12 To test whether it is the case for wheat Grx and Trx and to develop a synergetic system using food source Grx and Trx as enzymatic additives in food processing, the reduction assay of wTrx by wGrx was initially carried out.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Cold-active microbial enzymes have attracted increasing attention in recent years (Wang et al, 2012) since it is advantageous to use the cold-active enzymes owing to the reduced energy expenditure and processing costs associated with industrial heating steps besides the properties related to their structural characteristics (Duarte et al, 2013). Lowtemperature active endoglucanases are obtained from several fungal strains inhabiting the marine sponge Haliclona simulans in Ireland (Baker et al, 2010), and cold-active xylanase is produced by a marine-derived Cladosporium sp.…”
Section: Cold-active Microbial Enzymesmentioning
confidence: 99%